DIGITAL CARTEL IN THE FINTECH P2P LENDING INDUSTRY: Review of KPPU Decision Number 05/KPPU-I/2025 and the Sufficiency of Article 5 of Law No. 5 of 1999 - Sulung Nugroho; Setiyo Utomo; Deny Slamet Pribadi (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The digital economic transformation has driven the rapid growth of the peer-to-peer (P2P) lending fintech industry in Indonesia. However, alongside this growth, price-fixing coordination practices have emerged through the self-regulation mechanisms of industry associations, potentially violating competition law. This study examines the Business Competition Supervisory Commission (KPPU) Decision Number 05/KPPU-I/2025, which imposed sanctions on 97 P2P lending fintech companies for engaging in an interest rate-fixing cartel through the code of conduct of the Indonesian Joint Funding Fintech Association (AFPI). This research aims to construct these interest rate-fixing practices as a form of digital cartel and to assess the adequacy of Article 5 of Law Number 5 of 1999 in addressing digital cartel practices. This study employs normative legal research using a statutory approach and a case approach. The legal materials consist of primary legal sources, namely Law No. 5 of 1999 and KPPU Decision No. 05/KPPU-I/2025, as well as secondary legal sources including books, journals, articles, and antitrust doctrines. The analysis techniques applied are interpretive and argumentative, using legal reasoning. The results indicate that the interest rate-fixing practice through AFPI's self-regulation mechanism can be constructed as a digital cartel. This is because the association's code of conduct serves as a medium for price coordination among competitors, the interest rate ceiling aligns price expectations and strategies resulting in behavioral alignment, and the state action doctrine defense is applicable due to the absence of explicit delegation of authority and active state supervision. Furthermore, this study finds that Article 5 of Law No. 5 of 1999 has limitations in reaching digital cartel practices, particularly regarding the evidence of the "agreement" element, which is traditionally difficult to establish in coordination mediated by associations and self-regulation. Consequently, a reinterpretation of the price-fixing concept and a more adaptive legal reform tailored to digital market characteristics are required, including regulations concerning algorithmic collusion and the role of industry associations in price coordination.